ASUHAN KEBIDANAN KOMPREHENSIF PADA IBU DENGAN PERSALINAN - Cut Melda; Juliastuti Juliastuti; Yushida Yushida; Satrina Wati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The primary indicator for assessing the success of health development in a country is the maternal mortality rate (MMR), calculated based on the number of maternal deaths during pregnancy, childbirth, and the postpartum period, both due to congenital diseases and complications, per 100,000 live births. According to a World Health Organization (WHO) report, maternal mortality will remain a global public health problem until 2023. Data from the West Aceh Health Office indicates that in 2025, the maternal mortality rate will reach 5. The infant mortality rate in 2025 will be recorded at 34, with the most common causes being asphyxia and low birth weight (LBW). Efforts to accelerate the reduction in MMR and IMR include ensuring maternal access to quality health services, assisted delivery by trained health personnel, postpartum and neonatal care, an effective referral system, and family planning services, including postpartum family planning. Based on this description, researchers are interested in implementing Comprehensive Midwifery Care during pregnancy, childbirth, newborn care, and the postpartum period, including family planning counseling for postpartum mothers.